Experimental speciation study of natural gas oxidation using a single pulse shock tube. Issue 7 (11th March 2021) - Mehta, Jai M.; Brezinsky, Kenneth
Abstract: An experimental shock tube study of natural gas (NG) oxidation for several NG samples was carried out at nominal reaction pressures of 50–60 atm and temperatures ranging from 1100 to 1750 K over a nominal reaction time of 2.5 ms. As NG has no standard specified composition, various samples of NGs taken from the gas supply system across the United States were studied near stoichiometric conditions. In addition, a speciation study at equivalence ratios ranging from fuel lean ( φ ≈ 0.5) to pyrolysis of a representative NG sample was carried out to provide a comprehensive but nonexhaustive set of experimental data, which will be useful in optimizing chemical kinetic models for NG. Temperature‐dependent species yields measured in these experiments were compared with predictions from four well established chemical kinetic models. The agreement with model predictions was found to be largely inconsistent from experiment to experiment, reinforcing the need for optimization of models using comprehensive experimental data before their use predicting the oxidation products of NG.